The Influence of Income and Risk Perception on The Interest to Saving in Sharia Banking in Mandailing Natal District - Sari, Erika; Dewi, Meutia; Fuad, Muhammad (Pascasarjana Universitas Pasundan, 2023)
This study aims to determine the effect of income and risk perception on the intention to save in Islamic banking in the Mandailing Natal District. The sample in this study amounted to 96 respondents. The data analysis method uses multiple linear regression analysis with the regression equation, namely Y = 5.199 + 0.150X1 + 0.351X2. From the t test it is known that income and perceived risk partially have a significant1 effect on the intention to save in Islamic banking in the Mandailing Natal District. From the F test it is known that income and risk perception simultaneously have a significant1 effect on the intention to save in Islamic banking in Mandailing Natal Regency. Income and risk perception affect the intention to save in Islamic banking in Mandailing Natal Regency by 58.6%, while the remaining 41.